Uji Efektivitas Daun Sirih Dalam Menghambat Pertumbuhan Layu Bakteri Ralstonia solanacearum Pada Tanaman Terung - Andi Sintalydiawati; Dewi Fitriyanti; Elly Liestiany (www.ulm.ac.id, 2024)
Ralstonia solanacearum is one of the important diseases in eggplant plants which causes bacterial wilt in plants so control efforts need to be taken. One alternative control method is using vegetable pesticides from betel leaf powder. This research aims to determine the effectiveness of betel leaves in inhibiting the growth of R. solanacearum bacterial wilt on eggplant plants. This research used a Completely Randomized Design (CRD) with 5 treatments and 5 replications, each replication using 4 plants so there were 100 experimental units. The treatment used doses of 25 gr, 50 gr, 75 gr, 100 gr of betel leaf powder, and as a comparison, namely the control treatment in this study. Observations were made every day after inoculation to see the incubation period that occurred in the eggplant plants and once a week to observe the disease intensity and severity of the disease in the eggplant plants. The results of this study showed that an effective treatment with a dose of 100 g of betel leaf powder with an eggplant plant age of 47 days after showed the lowest treatment in suppressing Ralstonia solanacearum bacteria, namely a disease intensity percentage of 15% with a disease severity percentage of 20% and had the lowest incubation period. slow, namely 19 days, this shows that betel leaves have an effect in suppressing disease attacks caused by R. solanacearum on eggplant plants because they have antibacterial active compounds.